Innovative Approach to Javanese Language Learning: Exploring the Potential of Mobile-Assisted Language Learning - Lucia Yuyun Dian Susanti; Ida Zulaeha; Teguh Supriyanto; Rahayu Pristiwati (Universitas Negeri Semarang, 2023)
Currently, the development of learning that prioritizes technology, especially in online learning whose learning process is limited to delivering one-way material and assigning assignments. The learning process of writing Javanese literature has a big challenge because the delivery of material must have interaction in it so that teachers must be more creative and innovative to find the application of appropriate learning media. This study presents a systematic review of mobile assisted language learning (MALL) research in the field of Javanese literature learning at the high school level that can facilitate the development of creative reading and writing. This article also examines and reports on educational technology issues that may limit the development of reading and writing in a MALL-based Javanese language learning environment. The result of this study is a research on the use of MALL in aspects of learning to read and write creatively Javanese at the high school level. This article concludes that the use of interactive multimedia in language learning can be an effective strategy to improve student learning outcomes. The researchers also recommend further research to explore the use of interactive multimedia in different language learning contexts.